Reviews - Nola Campbell; Trevor Billany; Bronwyn Hegarty (Flexible Learning Association of New Zealand, 2012)
Reviews of Garrison, D. R., & Anderson, T. (2003). E-Learning in the 21st century: A framework for research and practice. London: Routledge Falmer Moore, M. G., & Anderson, W. G. (2003). Handbook of distance education. Mahwah, New Jersey: Lawrence Erlbaum Associates Reeves, T., & Hedberg, J. (2003). Interactive learning systems evaluation. Englewood Cliffs, New Jersey: Educational Technology Publications